A pressurized liquid extraction approach followed by standard addition method and UPLC-MS/MS for a fast multiclass determination of antibiotics in a complex matrix. (November 2018) - Ezzariai, Amine; Riboul, David; Lacroix, Marlène Z.; Barret, Maialen; El Fels, Loubna; Merlina, Georges; Bousquet-Melou, Alain; Patureau, Dominique; Pinelli, Eric; Hafidi, Mohamed
Abstract: In this work a fast analytical method for the determination of macrolides, tetracyclines and fluoroquinolones in a compost originating from a mixture of sewage sludge, palm waste and grass was developed by ultra-high performance liquid chromatography coupled to mass spectrometry (U-HPLC/MS). Antibiotics were extracted from compost by using the accelerated solvent extraction (ASE). The chromatographic separation was carried out on a T3 Cortecs C18 column using a mobile phase gradient mixture of water acidified with 1% of formic acid and acetonitrile. Recoveries of 24–30%, 53–93%, 33–57%, 69–135% and 100–171% were obtained for roxithromycin (ROX), chlortetracycline (CTC), oxytetracycline (OTC), enrofloxacin (ENR) and ciprofloxacin (CIP), respectively. As the most part of antibiotics showed significant matrix effect (ME), the method was validated using the standard addition method (SAM) to correct the observed ME. Instrumental variation, of LC/MS system, showed that 93.75% of the relative standard deviation (RSD %) are below 15%, although the organic load of extracts. This analytical method was applied to assess the fate of antibiotics during composting. Two composting experiments were conducted separately after spiking sludge at 2 different concentrations levels. The resulting elimination rates were of 52–76, 69–100, 100 and 24–50% for ROX, CTC, OTC and CIP, respectively. These results suggest that composting process contributes to the removal of residuals concentrations of macrolides and tetracyclines while the fluoroquinolones persist in the final compost product. Highlights: A fast and multiclass approach for the determination of antibiotics was developed. Standard addition method is an alternative to overcome matrix effect in compost. The analytical approach was not effective for fluoroquinolones. Macrolides and tetracyclines were removed significantly after composting. Fluoroquinolones removal is not significant and still persists in the final compost.